Prediction of pore pressure using well logs and seismic data in Fabi Field, Onshore Niger delta, Nigeria - Emmanuel, Aniwetalu; Emmanuel, Anakwuba; Juliet N, Ilechukwu; Okoye, Chidozie (International Journal of Advanced Geosciences, 2016)
The variations of pore pressure in Fabi Field Onshore Niger delta have been investigated using well log and seismic data. The both data were calibrated to ensure reasonable match in depth. Zones of overpressure were predicted from the well logs based on the deviations of petrophysical measurement from normal compaction trends. The lateral variations of the overpressure were delineated from seismic data through elastic impedance inversion. Overpressure cube was delineated from the inverted volumes through points of picked horizons. The results of the study revealed overpressure occurrence in well logs at depth level of 8625ft to 9000ft. The elastic impedance inversion presents overpressure variations beyond well control point at the depth level of about 1940-1140ms corresponding to very high impedance value of about 25540-27067ft/s*g/cc. The area extents of the positive anomalies (increase in elastic impedance) are mostly consistent with overpressure zones. Overpressure zones were also estimated from the seismic data between 1560ms -1600ms within the TRK-1 and TRK-2 horizon which also correspond to the well control points (8625ft to nearly 9000ft). The velocity and density crossplots revealed that undercompaction is the main overpressure generating mechanism in Fabi Field, although other parts of the field revealed unloading mechanism.